Influence of Soil-Structure Interaction on the Seismic Response of a Continuous Bridge with Friction Pendulum System - Bing Li; Chong Fu; Guolong Liu; Wei Wei; Junfa Duan; Bin Wang (Shock and Vibration)
A three-dimensional finite element analysis was carried out for the influence of soil-structure interaction (SSI) on the seismic response of an isolated continuous bridge with a friction pendulum system (FPS). SSI was modelled using the soil resistance vs deflection nonlinear springs (following p-y curves). The influence of SSI on the dynamic behaviour and the seismic response of isolated bridges with different friction coefficients of FPS were investigated using six measured ground motions. Results show that the effect of SSI is limited on the isolation period of the bridge, but significant on the response amplitude of the bridge structures, and particularly on the response amplitude at the pier top and bottom. The displacement and acceleration at the pier top are underestimated, while the shear force and bending moment at the pier bottom are overestimated if the SSI effects are ignored, which suggests that SSI should be considered in the seismic analyses of continuous bridges.